PENENTUAN KALOR DARI CAMPURAN ARANG TEMPURUNG KELAPA DENGAN CANGKANG KELAPA SAWIT DI TINJAU DARI PERBANDINGAN CAMPURANNYA - Doni Pandra; Sugianto '; Maksi Ginting (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been  carried  to determine the  calory  value of the  mixture of  coconut charcoal and palm oil shells  using an  experimental method. This experiment used a bomb callorimeter  to measure the physical parameters  of the sample (callory value, sulfur  total, total ash  and total moisture  of  content). Each sample was  treated  by  the same pressure and volume.  The samples  were  taken from two different materials, namely  charcoal  of  coconut shells  and oil palm shells.  Four different samples  were made from  combination of  grain size  ratio  of 60  :  40 and 40 : 60.  The sample  A and C  were mixture of  coconut shell charcoal  and  charcoal oil palm shells  with  60: 40 ratio, while the sample B and D were mixture of coconut shell Charcoal and charcoal oil palm shells for 40: 60 ratio. Results of the test showed the value of the physical parameters i.e callory value, sulfur  total, total ash and total moisture of content respectively  for the sample A  were  6.379  calories cal/g, 0.18%, 1.43%, and  8.00%,  for  the sample B  were 5.732 calories cal/g, 0.22%,  1.30% and  8,48 %,  for  the sample C were  5.787 cal/g, 0.20%,  10,91%, and 7.19%,  and  for  the  sample  D  were  5.395 calories cal/g, 0.20%, 11.24%, and 7,07%.  The sample  A  had  larger  grain density so that the  grain samples were  more solid.  The denser  of the material was  the higher the value of the heat from the charcoal.  From the overall data  obtained, it was  indicated  that  the sample  A had the highest quality value compared to the other samples.